Impact of fiber optic dispersion on the performance of OFDM-QAM system - Al-Khateeb, Khalid A. Saeed; Akhter, Fowzia; Islam, Md. Rafiqul (2010)
The Performance of Orthogonal Frequency Division Multiplexing (OFDM) combined with Quadrature Amplitude Modulation (QAM) has been analyzed in presence of fiber optic dispersion. The influence of dispersion on the (OFDM) spectrum is investigated with fiber lengths, bit rates, no. of channels and source line widths. The inter-channel interference occurs due to dispersion-induced broadening of OFDM spectrum. The power penalty suffered by the system is evaluated at bit error rate, BER=10-9 for a single mode fiber operating at 1.55μm. The results obtained from the OFDM-QAM system demonstrate that the influence of dispersion is lower in OFDM-QAM spectrum in comparison with single bit transmission with same bandwidth and it is approximately two times less than that of a conventional system.